Prevalence of menstrually-related migraine in a population of students from a municipal university center in the interior of Brazil - Tavares, Isabela Silva; Germano , Ariana Pereira; Bordini , Carlos Alberto (Headache Medicine, 2021)
Objective To identify the prevalence of migraine associated to menstruation in a population of students at a college in Brazil’s inland. Methods The students were recruited and submitted to the Test for the Identification of Women with Menstrual Period-Related Headache based on the ID-MigraineTM and Menstrual Migraine Assessment Tool questionnaires. Migraine diagnosis was made according to ICHD-3 criteria. Results Of the 424 students, 312 (73.5%) answered affirmatively in at least two of the four questions in the first part of the questionnaire and in the following 216 (69.2%) of these reported having migraine related to their menstrual period in the majority of the months. Conclusions Menstrual migraine is a prevalent public health problem that deserves attention in order to ensure a better quality of life for women affected by such a condition.